Distal femoral extension osteotomy and patellar tendon advancement or shortening in ambulatory children with cerebral palsy: A modified Delphi consensus study and literature review. (December 2022) - Rutz, Erich; Novacheck, Tom F; Dreher, Thomas; Davids, Jon R; McCarthy, James; Kay, Robert M; Shore, Benjamin J; Shrader, M Wade; Veerkamp, Matthew; Chambers, Hank; Narayanan, Unni; Pierz, Kristan; et al.
Purpose: In children with cerebral palsy, flexion deformities of the knee can be treated with a distal femoral extension osteotomy combined with either patellar tendon advancement or patellar tendon shortening. The purpose of this study was to establish a consensus through expert orthopedic opinion, using a modified Delphi process to describe the surgical indications for distal femoral extension osteotomy and patellar tendon advancement/patellar tendon shortening. A literature review was also conducted to summarize the recent literature on distal femoral extension osteotomy and patellar tendon shortening/patellar tendon advancement. Method: A group of 16 pediatric orthopedic surgeons, with more than 10 years of experience in the surgical management of children with cerebral palsy, was established. The group used a 5-level Likert-type scale to record agreement or disagreement with statements regarding distal femoral extension osteotomy and patellar tendon advancement/patellar tendon shortening. Consensus for the surgical indications for distal femoral extension osteotomy and patellar tendon advancement/patellar tendon shortening was achieved through a modified Delphi process. The literature review, summarized studies of clinical outcomes of distal femoral extension osteotomy/patellar tendon shortening/patellar tendon advancement, published between 2008 and 2022. Results: There was a high level of agreement with consensus for 31 out of 44 (70%) statements on distal femoral extension osteotomy. Agreement was lower for patellar tendon advancement/patellar tendon shortening with consensus reached for 8 of 21 (38%) of statements. The literature review included 25 studies which revealed variation in operative technique for distal femoral extension osteotomy, patellar tendon advancement, and patellar tendon shortening. Distal femoral extension osteotomy and patellar tendon advancement/patellar tendon shortening were generally effective in correcting knee flexion deformities and extensor lag, but there was marked variation in outcomes and complication rates. Conclusion: The results from this study will provide guidelines for surgeons who care for children with cerebral palsy and point to unresolved questions for further research. Level of evidence: level V.